If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(x + -9) = -42 Reorder the terms: -6(-9 + x) = -42 (-9 * -6 + x * -6) = -42 (54 + -6x) = -42 Solving 54 + -6x = -42 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-54' to each side of the equation. 54 + -54 + -6x = -42 + -54 Combine like terms: 54 + -54 = 0 0 + -6x = -42 + -54 -6x = -42 + -54 Combine like terms: -42 + -54 = -96 -6x = -96 Divide each side by '-6'. x = 16 Simplifying x = 16
| 7+8(4+4x)=6x-39 | | -8a+6a+42=1 | | 4x-3(x-1)=-4+3x+11 | | Fx=10x^2+8x+8 | | 22/2= | | 3x(x^2+2x-6)+4(x^2-6x+2)= | | g(x)=3.4x-8 | | 20n=10n^2 | | 2.2m=19.8 | | 13x+5=-35 | | 6=2(v+8)-4v | | 4(6y+1)+8=6(2y+5)-5 | | 0.9(5x+15)2.5-(x+3)= | | x^6+8y^3= | | (12y^3)+(24y^2)=3y+6 | | X+2x+(2x+30)=280 | | -x=4x-3 | | 4+3x-2=8x+18-3x | | -8=-8(2x-7) | | 93=(93)(63) | | st+3y=6 | | 8-3(1-3m)= | | 1.8+7n=9.5-4bn | | 0.60p+80=0.70+30 | | 2(6x-2)=3(5x-5) | | 6y^2+1y-2=0 | | Y=157.5x+50 | | 0.8y=-4 | | [-5/8][-8/15]= | | 1=-1.5+0.5y | | x^4-5x^3-9x^2+45x= | | 1/2+(2/3)(3/4)-(4/5)(5/6)= |